Impact of highly and less job-related diversity on work group cohesion and performance: a meta-analysis - Webber, Sheila Simsarian; Donahue, Lisa M. (Journal of Management, 2001)
A meta-analysis of the data from empirical investigations of diversity in work groups was used to examine the impact of two types of diversity attributes, highly job-related and less job-related, on work group cohesion and performance. This distinction was used to test the proposition that different types of diversity will differentially impact work group cohesion and performance. In addition, type of team was examined as a possible moderator of the relationship between diversity and performance. Results showed that neither type of diversity had a relationship with cohesion or performance. Explanations and directions for future research are offered.